Functional Connectivity Abnormalities of Brain Regions with Structural Deficits in Young Adult Male Smokers - Bu, Limei; Yu, Dahua; Su, Shaoping; Ma, Yao; von Deneen, Karen M.; Luo, Lin; Zhai, Jinquan; Liu, Bo; Cheng, Jiadong; Guan, Yanyan; Li, Yangding; Bi, Yanzhi; et al. (Frontiers in Human Neuroscience, 2016)
Smoking is one of the most prevalent dependence disorders. Previous studies have detected structural and functional deficits in smokers. However, few studies focused on the changes of resting state functional connectivity (RSFC) of the brain regions with structural deficits in young adult smokers. Twenty-six young adult smokers and 26 well-matched healthy non-smokers participated in our study. Voxel-based morphometry (VBM) and RSFC were employed to investigate the structural and functional changes in young adult smokers. Compared with healthy non-smokers, young smokers showed increased gray matter (GM) volume in the left putamen and decreased GM volume in the left anterior cingulate cortex (ACC). Moreover, GM volume in the left ACC has a negative correlation trend with pack-years and GM volume in the left putamen was positively correlated with pack-years. The left ACC and putamen with abnormal volumes were chosen as the regions of interest (ROIs) for the RSFC analysis. We found that smokers showed increased RSFC between the left ACC and right amygdala and between the left putamen and right anterior insula. We revealed structural and functional deficits within the frontostriatal circuits in young smokers, which may shed new insights into the neural mechanisms of smoking.